2022
DOI: 10.34031/2071-7318-2022-7-12-39-45
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Compliance With the Requirements of the Norms for the Internal Microclimate of a Corner Room

Abstract: The article considers the buildings of medical and preventive, children's educational and educative institutions. The resistance to heat transfer of the windows is not increased for such buildings at the last change in the norms of thermal protection in the Russian Federation in 2018. In this regard, it is important to check compliance with the requirements of regulatory documents for radiation temperature and asymmetry of the radiation temperature at the boundary of the serviced area of the premises of such b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In [14] an ordinary room of the same geometry as the corner one (the 5.4 m long wall is internal) has been examined. Comparison of the calculation results of the ordinary and corner rooms showed that the influence of the second window on the radiation temperature local asymmetry is noticeable.…”
Section: Methodsmentioning
confidence: 99%
“…In [14] an ordinary room of the same geometry as the corner one (the 5.4 m long wall is internal) has been examined. Comparison of the calculation results of the ordinary and corner rooms showed that the influence of the second window on the radiation temperature local asymmetry is noticeable.…”
Section: Methodsmentioning
confidence: 99%